Cost-Effectiveness Analysis of Rivaroxaban in Chinese Patients With Stable Cardiovascular Disease - Feng, Tianyu; Zheng, Zhou; Gao, Shang; Xu, Jiaying; Cao, Pen; Jia, Huanhuan; Yu, Xihe (Frontiers in Pharmacology, 2022)
Objective: This study aimed to investigate the cost-effectiveness of low-dose rivaroxaban plus aspirin versus aspirin alone for patients with stable cardiovascular diseases in the China. Methods: We used TreeAge 2019 to construct a Markov model to assess the direct healthcare costs and quality-adjusted life years for three therapies, namely low-does rivaroxaban plus aspirin, rivaroxaban alone, and aspirin alone. Transitional probabilities were derived from the COMPASS trial, and the costs and utilities were obtained from the Chinese Health Care Statistical Yearbook and published studies. Use the Incremental cost-effectiveness ratio to describe the results. The willingness-to-pay threshold is set at US11,000 (China's 2020 Gross National Product per capita). Result: In patients with stable cardiovascular disease, the increased cost per quality-adjusted life year gained in the low-dose rivaroxaban combined with aspirin group compared to the aspirin alone group was US7937.30. The increased cost per quality-adjusted life year gained in the rivaroxaban alone group versus the aspirin alone group was US15,045.78. Conclusion: A low-does rivaroxaban plus aspirin therapy may be cost-effective in the secondary prevention of stable cardiovascular disease in patients.